PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMEN DIVISIONAL (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 031 TARAIBANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Dedi Suryadi; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT:This research is motivated by the low yields seen students learning mathematics average value of 61.86 students from 30 students while the minimum completeness criteria (KKM) 70.The purpose of this study was to improve the mathematics learning outcomes Elementary School fourth grade students 031 Taraibangun Mining District of Kampar District Cooperative Learning Model with Student Teams Achievement Divisional (Stad). Research carried out in March of the academic year 2014/2015 in 031 Taraibangun Elementary School in the fourth grade. The instrument used in this study is a teacher and student activity sheets as well as learning about the test results. Pelitian data analysis technique is descriptive analysis techniques. This study presents an increase in the activity of teachers in the first cycle of the first meeting of teachers activity 42.86% with less category, at the second meeting increased 57.14% with enough categories, pertemuanketiga second cycle increased to 78.57% with the good category once, at the fourth meeting teacher activity increased to 100% with the good category yet. Student activity based on the results of the study in the first cyclestudent activity only 39.29%, at the second meeting increased to 57.14%.Whereas the second cycle of the third meeting of the percentage of student activity increased to 75.00%, and the fourth meeting of student activity increased to 96.43%. Student learning outcomes in basic score, an average of 61.86. At the end of the first cycle Deuteronomy average value of student learning outcomes increased to 66.33, and at the end of the repeat second cycle increased to 75.66. The above data indicate that the Application of Cooperative Learning Model achievemen Divisional Student Teams (Stad) can Improve learning outcomes Mathematics Grade IV State Primary School 031 Taraibangun Mining District of Kampar.Keywords : Cooperative type achievemen Student Teams Divisional Results Learning Math Students.